MENINGKATKAN KESADARAN MASYARAKAT TENTANG ISU DISABILITAS DI INDONESIA - Novan Ariel; Kaelan Gafhar Yusuf Islam (Empat Sembilan Publisher, 2024)
Objective: This study aims to formulate the concept of the most appropriate approach in efforts to respect, protect and fulfill the rights of persons with disabilities as well as the concept of policies that are responsive to persons with disabilities, especially women and children with disabilities. Method: this study uses a qualitative approach with literature and direct observation methods to study disability in Indonesia, this approach was chosen because it allows researchers to gain insight into disability issues in depth from various perspectives both from academic journal sources and real observers of direct observation. Results: Through a qualitative approach, the results of this study are; 1. Offer to apply the concept of inclusion to answer the problems of violence, marginalization and discrimination against persons with disabilities. Inclusion has conditions for a positive social environment, accessibility and affordability of the physical environment in the form of buildings and infrastructure. Social inclusion that is inseparable from history and experience is based on the beliefs, values and cultures of the diverse Indonesian people. 2. Responsive public policies for the protection and fulfillment of the rights of persons with disabilities are a legal guarantee for the implementation of participatory public programs and services. Inclusive responsive policies that are able to place people with disabilities as part of diversity and are able to play a social role, contribute positively to development. Conclusion: People with disabilities have equal rights with others. Even so, discrimination is still often felt because they are considered not independent. In order to achieve independence, people with disabilities do work to meet the needs of life and improve social skills. The lack of availability of jobs for people with disabilities makes people with disabilities prefer to work in the business sector. The existence of law no. 8 of 2006 makes several people with disabilities work in a company. This is a challenge for people with disabilities because they must be able to adapt to the work environment. Meeting new people is certainly not an easy thing. Discrimination that has been felt by people with disabilities can certainly hinder the process of self-adjustment. Therefore, social workers can play a role in increasing people's capacity to overcome the problems they face and connect the resources around them to help overcome problems.